%TTD and %TUDD: New SAS macro programs to calculate the survival data of the time to deterioration for patient-reported outcomes data in oncology. (February 2022) - Charton, E.; Falcoz, A.; François, E.; Touraine, C.; Bachet, J.-B.; Louvet, C.; Hamidou, Z.; Bascoul-Mollevi, C.; Anota, A.
Highlights: The new SAS macro programs, %TTD and %TUDD, calculate the time to deterioration. Several definitions of deterioration were implemented following the recent recommendations published. These macros can be applied to any patient-reported outcome questionnaire. To our knowledge, these are the first SAS macros implementing this method. These macros help to move toward the goal of standardization. Abstract: Background and objective: Longitudinal analysis of patient-reported outcome (PRO) data remains challenging, as no standardization of statistical methods has been proposed, making comparison of PRO results between clinical trials difficult. In this context, the time to deterioration approach has recently been proposed and is regularly used as a modality of longitudinal PRO analysis in oncology. Methods: Two new SAS macro programs were developed, %TTD and %TUDD, which implement longitudinal analysis of PRO data according to the time to deterioration approach. These programs implement the recommended deterioration definitions. We described the programs with their different functionalities. Results: The %TTD macro calculates the time to first or transient deterioration, and the %TUDD macro calculates the time until definitive deterioration. These macros allow to obtain the survival variables from the time to deterioration approach. We illustrate our programs by presenting different applications on the randomized phase II AFUGEM GERCOR clinical trial. Conclusion: The implementation of the deterioration definitions in SAS software allows the dissemination of this approach, in order to move toward the goal of standardization of longitudinal PRO analysis in oncology clinical trials.